Peran Orang Tua dalam Pembentukan Literasi Finansial Anak Usia Dini pada Suku Baduy - Mutaqin, Moh Fikri Tanzil; Sari, Novita; Saputra, Desma Yuliadi (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2021)
This research aims to examine the role of parents in forming financial literacy in early childhood among the Baduy tribe, which has unique cultural characteristics and traditional values. Financial literacy in the Baduy community does not just focus on the concept of money and economic transactions, but includes an understanding of natural resource management, the value of simplicity, and the principle of togetherness. Using a qualitative approach with a case study design, this research involved in-depth interviews, participant observation, and document analysis to obtain data regarding the role of parents in teaching financial literacy. The research results show that parents in the Baduy tribe teach financial literacy through example, daily activities, and traditional principles that encourage children to respect resources, prioritize community needs, and live a balanced life. Financial literacy in this context is oriented towards strengthening social values and sustainability, not on the accumulation of material wealth. These findings provide insight that financial literacy in indigenous communities, such as the Baduy Tribe, integrates relevant local cultural values and emphasizes the importance of life balance and sustainability. This research suggests the importance of developing financial literacy programs based on local wisdom to support the cultural sustainability and welfare of indigenous communities.